Determination of the Physicochemical Quality of Groundwater and its Potential Health Risk for Drinking in Oromia, Ethiopia - Binyam Gintamo; Mohammed Azhar Khan; Henok Gulilat; Rakesh Kumar Shukla; Zeleke Mekonnen (SAGE Publishing, 2022)
This study aimed to determine the physicochemical quality of groundwater and its potential health risk for drinking in Oromia, Ethiopia. The groundwater samples were collected from 17 sampling stations in the dry and wet season in the Sebeta zone, Oromia, from March to August 2020. Metals and physicochemical parameters, and selected heavy metals, such as iron (Fe), copper (Cu), manganese (Mn), chromium (Cr), zinc (Zn), and lead (Pb) were monitored. The data were analyzed using multivariate statistical methods (Pearson's Correlation and T-test). The means seasonal variations were higher in the dry season than in the wet season except for pH and Turbidity. The variation was significant for most parameters except Pb, Zn, chlorine, Total Alkaline, Magnesium Hardness, Calcium Hardness ), and Turbidity. There was a strong and positive correlation between Total dissolved solids (TDS) and Conductivity), (pH and Cr), (T.H. and Magnesium (Mg)), (bicarbonate and Calcium (Ca), (Zn and Turbidity) in the dry season; and (T.H. with Potassium (K), (Pb and Fe); (bicarbonate and T.H.); (Ca and Mg); (Na and T.A.,) in the wet season. The hazard index (H.I.) values in the dry season (HI = 1.331) were higher than in the wet season (HI adults  = 0.075). Likewise, the H.I. (dry season) was higher (HI children  = 1.861) than in the wet season (HI children  = 0.105). Chronic groundwater exposure at drinking sources in the dry season is a potential health risk to humans in general and is relatively high for children. Urgent management and close monitoring are required for drinking groundwater sources and other nearby residents' safety areas.